Fundamentals of GPS Receivers A Hardware Approach - Doberstein, Dan (Springer New York : Imprint: Springer, 2012)
While much of the current literature on GPS receivers is aimed at those intimately familiar with their workings, this volume summarizes the basic principles using as little mathematics as possible, and details the necessary specifications and circuits for constructing a GPS receiver that is accurate to within 300 meters. Dedicated sections deal with the features of the GPS signal and its data stream, the details of the receiver (using a hybrid design as exemplar), and more advanced receivers and topics including time and frequency measurements. Later segments discuss the Zarlink GPS receiver chip set, as well as providing a thorough examination of the TurboRogue receiver, one of the most accurate yet made. Guiding the reader through the concepts and circuitry, from the antenna to the solution of user position, the book's deployment of a hybrid receiver as a basis for discussion allows for extrapolation of the core ideas to more complex, and more accurate designs. Digital methods are used, but any analogue counterparts are assessed alongside them, and the author shows how GPS receivers and satellites are more concerned with time and movement than physical position in space.